Deep Sequential Models for Task Satisfaction Prediction - Mehrotra, Rishabh; Awadallah, Ahmed; Yilmaz, Emine; Shokouhi, Milad; Zitouni, Imed; El Kholy, Ahmed; Khabsa, Madian (The 26th ACM Conference on Information and Knowledge Management (CIKM 2017), 2017)
CIKM is a premier forum for research on topics at the confluence of information retrieval, data management, and knowledge management. This year, CIKM highlights technologies and insights that materialize the “Smart Cities, Smart Nations” vision shared by many urban areas and their countries, while we bring together international and Singapore technology providers and seekers to explore technology and business collaboration opportunities through open innovation.